Mapping the Cognitive Dimensions of Bilingual Speakers: An Exploration of Code-Switching Strategies at Bina Budaya Pontianak - Nina Kastria; Ikhza Mahendra Putra; Martono (Universitas Islam Negeri Palopo, 2026)
Code-switching studies have generally focused on socio-pragmatic aspects, leaving the cognitive dimension in bilingual speakers’ language decision-making relatively underexplored. In fact, language switching occurs through processes that interactively involve social, linguistic, and cognitive factors. To address this gap, this phenomenological qualitative study involved three active bilingual participants with backgrounds in Indonesian, English, Italian, Japanese, and Tagalog at Lembaga Bina Budaya Pontianak. Data were collected through in-depth interviews and participant observation and were subsequently analyzed using thematic analysis techniques. The findings indicate that executive control, working memory, and metacognitive awareness play significant roles in determining the timing and form of code-switching. Participants employed tag switching, inter-sentential switching, and intra-sentential switching adaptively in accordance with social context and communicative objectives, thereby enhancing semantic precision, maintaining social relations, and managing interactional nuances. Emotional factors and personal experiences also influenced language preferences. Theoretically, this study underscores the importance of a cognitive-phenomenological perspective in bilingualism research. Practically, these findings are relevant to the development of language instruction and intercultural communication. Thus, bilingualism may be understood as a communicative practice that involves the management of cognitive processes in determining language choice.